2019
DOI: 10.1128/jcm.01901-18
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Antigen Concentration Thresholds for Attributing Fever to Malaria among Outpatients in Angola

Abstract: The density of malaria parasites is a key determinant of whether an infected individual develops fever. While the pyrogenic threshold for malaria parasite density has been well studied, there are no analogous data on the antigen levels associated with fever during infection. Samples from 797 afebrile and 457 febrile outpatients from two provinces in Angola with known concentrations of histidine-rich protein 2 (HRP2), aldolase, and lactate dehydrogenase (LDH) antigens were analyzed by Bayesian latent class mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…Moreover, the ratios of pre- and post-day 2 clearance rates for LDH and Aldo are very similar, suggesting the two antigens might share a similar mechanism of clearance. The link between LDH and Aldo concentration and the presence of the parasite itself is consistent with the previous observation that LDH and Aldo levels are more closely associated with current parasite density, compared to HRP2, which can be interpreted more accurately as a measure of cumulative parasite load over the course of the infection [4, 19, 20].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the ratios of pre- and post-day 2 clearance rates for LDH and Aldo are very similar, suggesting the two antigens might share a similar mechanism of clearance. The link between LDH and Aldo concentration and the presence of the parasite itself is consistent with the previous observation that LDH and Aldo levels are more closely associated with current parasite density, compared to HRP2, which can be interpreted more accurately as a measure of cumulative parasite load over the course of the infection [4, 19, 20].…”
Section: Discussionsupporting
confidence: 88%
“…Point-of-care tests should be able to detect clinically relevant antigenemias (18) but not necessarily all antigenemias. A recent study showed that a PfHRP2-based RDT with an LOD in the range of 3 to 10 ng/ml would provide ideal sensitivity and specificity in diagnosing malaria infections at densities high enough to be the cause of fever (19). From this study, the LOD 50 estimates generally fall into this range, although the 75%, 90%, and 95% estimates exceed this range.…”
Section: Discussionmentioning
confidence: 62%
“…Figure 2a shows the probability of detection by uRDT in relation to HRP2 concentration for Mali in comparison to the studies conducted in Uganda and Myanmar [7,8]. Differences emerged in uRDT detection limits among the three study populations: there was a 50% probability of testing positive by uRDT at HRP2 thresholds of 207 pg/mL [95% credible interval (CrI) 160-268] in Mali, 15 pg/mL (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) in Uganda, and 101 pg/mL (66-156) in Myanmar. The established limit of detection (LOD) for the commercial Alere Malaria Ag P.f uRDT is 80-100 pg/mL, per laboratory evaluation by Das et al [15].…”
Section: Performance Of the Ultra-sensitive Rdtmentioning
confidence: 99%
“…RDTs have been considered to perform equivalently to microscopy in terms of sensitivity and specificity [ 6 ], with a recognition that HRP2-based RDTs may provide false positives due to the long half-life of circulating HRP2 [ 1 , 2 ]. The advent of new RDTs, such as the ultra-sensitive HRP2-based Alere™ Malaria Ag P.f RDT (Abbott, South Korea) with a tenfold lower limit of detection for HRP2 than previous RDTs [ 7 , 8 ] has incentivized the research community to better understand antigen dynamics in infected populations [ 8 12 ]. Concurrently, new assays for antigen quantification have been developed both as research tools on the Luminex platform [ 13 , 14 ] and as the commercially available Q-Plex™ Human Malaria Array (Quansys Biosciences, USA) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%